2013
DOI: 10.1177/1357633x13517350
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted home hazard assessment for fall prevention: a feasibility study

Abstract: We examined the feasibility of using a remotely manoeuverable robot to make home hazard assessments for fall prevention. We employed use-case simulations to compare robot assessments with in-person assessments. We screened the homes of nine elderly patients (aged 65 years or more) for fall risks using the HEROS screening assessment. We also assessed the participants' perspectives of the remotely-operated robot in a survey. The nine patients had a median Short Blessed Test score of 8 (interquartile range, IQR 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
0
15
1
Order By: Relevance
“…The use of non-clamping rugs and smooth and slippery floorings seems to be unaffected which reduces slippery floors. Sadasivam, according to the view of elderly, reported the bedroom’s light and a bright way from bed to toilets as risk factors [ 36 ], which was not consistent with the findings of the present study. Indirect electricity and lighting are used in Iranian homes, and almost all participants have enough light and brightness, especially in stairs, corridors and bathrooms in their homes.…”
Section: Discussioncontrasting
confidence: 99%
“…The use of non-clamping rugs and smooth and slippery floorings seems to be unaffected which reduces slippery floors. Sadasivam, according to the view of elderly, reported the bedroom’s light and a bright way from bed to toilets as risk factors [ 36 ], which was not consistent with the findings of the present study. Indirect electricity and lighting are used in Iranian homes, and almost all participants have enough light and brightness, especially in stairs, corridors and bathrooms in their homes.…”
Section: Discussioncontrasting
confidence: 99%
“…Sadasivam et al, 2014[61] proposed the development of a remote-controlled robot (Spykee) equipped with video camera and different sensors that passed over all types of flooring, including carpets. The purpose of the study was to see whether the robot was able to make an assessment of risks in the home by detecting potential hazards and preventing falls.…”
Section: Resultsmentioning
confidence: 99%
“…Studies varied markedly in terms of the psychometric data presented. Some authors reported criterion validity [ 49 , 62 , 110 , 112 , 120 , 124 ], others reported content validity [ 56 , 81 , 82 , 91 , 97 , 103 ] or predictive validity [ 27 ]. Only two authors reported sensitivity and specificity of checklists items [ 62 , 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…From these documents, 42 unique checklists were identified and included in the second stage of this review [ 8 , 15 17 , 20 23 , 34 , 44 , 49 , 51 , 53 , 58 , 66 , 69 , 72 , 79 , 82 , 86 , 87 , 98 , 102 , 108 , 110 112 , 115 , 121 , 124 , 126 , 132 , 135 , 137 , 139 , 140 , 144 , 148 – 152 ].…”
Section: Methodsmentioning
confidence: 99%